O caráter narrativo da Constituição: identidade narrativa e Constituição justa a partir de Paul Ricoeur - Guimarães Filho, Gilberto (Universidade do Vale do Rio dos Sinos, 2016)
The constitutional studies have as a central concern about the Constitution the power limitation and the definition of fundamental rights. The importance of this is undeniable, however, this perspective is founded on liberal and contractualist ideas, which, together with science, exclude at the constitutional thinking narrative, symbolic and poetic elements and consequences. In this sense, we depart with the narrative theory, especially through narrative identity in Paul Ricoeur, in order to unveil hidden elements of the narrative character of constitutional thought. For this path, in the first chapter we understand what is narrative, its relationship to our identity as beings who narrate themselves (homo fabulans) and the dialectic between sameness and selfhood in Paul Ricoeur. Done this step, the second chapter will enter into the debate on democratic Constitution from the debate between Hans Kelsen and Carl Schmitt, focusing on atomism and pluralism in Kelsen and the unity of the people in Schmitt, to reconstruct the constitutional thinking such a thought about a politics fundamental narrative, identifying various issues as narratives issues. In the third and final chapter entering the consequences of Ricoeur’s Little Ethics, we replace the issue of democratic constitution in search of what would be a fair Constitution and its circular relationship with a collective promise that unites the nation (Schmittian democratic constitution element) and, at the same time ensuring pluralism (kelsenian democratic constitution element). The fair Constitution which combines a common narrative and several unique narratives, recognizing them politically.
Keywords: Teoria constitucional; Hermenêutica filosófica; Narrativa; Constituição; Pluralismo; Constitutional theory; Philosophical hermeneutics; Narrative; Constitution; Pluralism; ACCNPQ::Ciências Sociais Aplicadas::Direito